Gang Transitions and Transformations in an International Context 2016
DOI: 10.1007/978-3-319-29602-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Flemish Youth Participate in Right-Wing Disruptive Groups?

Abstract: The events of 9/11 gave rise to an increase in studies on political violence and terrorism. Horgan (2005), Bouhana & Wikström (2010)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Both ethnocentrism and thrill-seeking have a positive effect on exposure to racist peers, with the effect of ethnocentrism being considerably stronger (β = .42) than the effect of thrill-seeking (β = .16). Often, scholars favor a “birds of a feather flock together” interpretation (Bjørgo, 1997, 2002; De Waele & Pauwels, 2016). This is logical from a theoretical point of view, given that ethnocentrism is operationalized as negative attitudes toward the out-group, and association with racist peers can result in an approval of these attitudes, thus heightening self-esteem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ethnocentrism and thrill-seeking have a positive effect on exposure to racist peers, with the effect of ethnocentrism being considerably stronger (β = .42) than the effect of thrill-seeking (β = .16). Often, scholars favor a “birds of a feather flock together” interpretation (Bjørgo, 1997, 2002; De Waele & Pauwels, 2016). This is logical from a theoretical point of view, given that ethnocentrism is operationalized as negative attitudes toward the out-group, and association with racist peers can result in an approval of these attitudes, thus heightening self-esteem.…”
Section: Resultsmentioning
confidence: 99%
“…Self-reported political violence was measured using the scale used by Gavray, Fournier, and Born (2012), De Waele and Pauwels (2016), and Pauwels and Schils (2016). Respondents were asked if they ever had done certain things, such as, for example, “vandalized anything in the street or at the public transport stations (e.g., bus stops, bicycles, streetlights, or something else),” “participated in a political action that was not allowed,” “thrown stones at the police during a demonstration?” “destroyed something on the streets because of your political or religious belief,” “damaged someone’s property because of your political or religious belief,” and “set something on fire because of your political or religious belief.” In the present study, we summarized all scale items and created a variety scale, which is common practice in juvenile delinquency research.…”
Section: Measurement Of Conceptsmentioning
confidence: 99%
“…There is now a small but growing body of research showing that perceived racial discrimination leads to offending among minority groups, and it is therefore likely that other kinds of discrimination and injustice affect offending and antisocial conduct in general, not only in minority groups. De Waele and Pauwels (2016), Pauwels and Heylen (2017) and Doosje, Loseman and Van den Bos (2013) demonstrated that measures of perceived injustice negatively affected perceptions of personal respect (that is, the feeling that one is respected as a human being). Taken together, these findings suggest that perceived injustices will increase negative emotions (towards out-groups) that contribute to political violence.…”
Section: The Crystallization Of Discontent and Low Self-control As Camentioning
confidence: 99%
“…Since the September 11 attacks in 2001, a multitude of studies have been conducted on political violence, especially on the field of Islamist terrorism (Baker, 2003; Khosrokhavar, 2015; Wiktorowicz, 2005). Contemporary studies on far-right extremism have paid a lot of attention to explaining individual differences in (permissive attitudes towards the use of) violence (De Waele and Pauwels, 2016; Heitmeyer, 2003). This led many policy makers to see other forms of politically or religiously motivated aggression as a domain, thereby forgetting that plenty of studies have been conducted to explain and understand participation in racist and far-right movements (for example, Blee, 2007; McGirr, 2015; Suttmoeller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is a valid criticism of studies of violent extremism that is recognized in studies on political and religious violence. It has been stated before that studies of political violence can learn from criminological studies (Decker & Pyrooz, 2015; De Waele & Pauwels, 2016).…”
Section: Introductionmentioning
confidence: 99%